2020
DOI: 10.21203/rs.3.rs-118180/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Involvement of the Extracellular Matrix Proteins Periostin and Tenascin C in Nasal Polyp Remodeling by Regulating the Expression of MMPs

Abstract: Background: Tissue remodeling caused by increased MMPs is involved in the pathogenesis of chronic rhinosinusitis with nasal polyposis (CRSwNP). We previously found higher levels of periostin and tenascin C in CRSwNPs, but whether they are associated with the dysregulation of MMPs is unknown. Therefore, the present study aimed to investigate the regulatory roles of two ECM proteins in the expression of MMPs in nasal polyps.Methods:The concentrations of MMP-2, MMP-3, MMP-7, MMP-8, MMP-9, MMP-12, MMP-13, TIMP-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…More recently, single cell gene expression studies have also revealed distinct populations of epithelial cells and lymphocytes uniquely contributing to CRS pathophysiology (117,118) . Transcriptional changes have largely been validated by proteomic studies (119)(120)(121) as well as cellular and histologic studies of sinonasal mucosa which have highlighted not only importance of inflammatory dysregulation, but tissue remodeling in CRS pathophysiology (122)(123)(124)(125)(126) .…”
Section: Recent Multiomic Approaches Applied To Crs Have Revealed Novel Insights Into the Pathophysiologic Mechanisms Of Crsmentioning
confidence: 99%
“…More recently, single cell gene expression studies have also revealed distinct populations of epithelial cells and lymphocytes uniquely contributing to CRS pathophysiology (117,118) . Transcriptional changes have largely been validated by proteomic studies (119)(120)(121) as well as cellular and histologic studies of sinonasal mucosa which have highlighted not only importance of inflammatory dysregulation, but tissue remodeling in CRS pathophysiology (122)(123)(124)(125)(126) .…”
Section: Recent Multiomic Approaches Applied To Crs Have Revealed Novel Insights Into the Pathophysiologic Mechanisms Of Crsmentioning
confidence: 99%